2015
DOI: 10.2147/cia.s80190
|View full text |Cite
|
Sign up to set email alerts
|

Transient cerebral ischemia in an elderly patient with patent foramen ovale and atrial septal aneurysm

Abstract: Cerebrovascular disease is one of the most common causes of cerebrovascular morbidity and mortality in developed countries; up to 40% of acute ischemic strokes in young adults are cryptogenic in nature – that is, no cause is determined. However, in more than half of these patients, patent foramen ovale (PFO) is seen along with an increased incidence of atrial septal aneurysm (ASA). The following is a report of an interesting case: a 68-year-old man with ASA and transient cerebral ischemia. Transesophageal echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…В связи с этим уместным является представление рекомендаций целевого назначения ЧПЭхоКГ, предложенных A. Merante с соавт. [293].…”
Section: взаимосвязи структурных аномалий сердца и их клиническое знаunclassified
“…В связи с этим уместным является представление рекомендаций целевого назначения ЧПЭхоКГ, предложенных A. Merante с соавт. [293].…”
Section: взаимосвязи структурных аномалий сердца и их клиническое знаunclassified
“…It is reported that PFO was associated with numerous disease processes including paradoxical embolism in cryptogenic stroke 4 , transient ischemic attack (TIA) 5 , latypnoea-orthodeoxia syndrome 6 , decompression sickness, migraine with aura and other venoarterial embolic phenomena 7 . Transcranial Doppler and transesophageal echocardiography (TEE) or transthoracic echocardiography (TTE) with the micro-bubbles test were commonly used methods to detect right-to-left shunt both at rest and during the Valsalva maneuver 8 9 . Since the original maneuver was first used by Valsalva in 1704, the VM has been widely used in clinical practice 10 .…”
mentioning
confidence: 99%